Muramyl Dipeptide Enhances Lipopolysaccharide-Induced Osteoclast Formation and Bone Resorption through Increased RANKL Expression in Stromal Cells - Masahiko Ishida; Hideki Kitaura; Keisuke Kimura; Haruki Sugisawa; Tomo Aonuma; Haruhiko Takada; Teruko Takano-Yamamoto (Journal of Immunology Research)
Lipopolysaccharide (LPS) is bacterial cell wall component capable of inducing osteoclast formation and pathological bone resorption. Muramyl dipeptide (MDP), the minimal essential structural unit responsible for the immunological activity of peptidoglycans, is ubiquitously expressed by bacterium. In this study, we investigated the effect of MDP in LPS-induced osteoclast formation and bone resorption. LPS was administered with or without MDP into the supracalvariae of mice. The number of osteoclasts, the level of mRNA for cathepsin K and tartrate-resistant acid phosphatase (TRAP), the ratio of the bone destruction area, the level of tartrate-resistant acid phosphatase form 5b (TRACP 5b), and C-terminal telopeptides fragments of type I collagen as a marker of bone resorption in mice administrated both LPS and MDP were higher than those in mice administrated LPS or MDP alone. On the other hand, MDP had no effect on osteoclastogenesis in parathyroid hormone administrated mice. MDP enhanced LPS-induced receptor activator of NF-κB ligand (RANKL) expression and Toll-like receptor 4 (TLR4) expression in vivo and in stromal cells in vitro. MDP also enhanced LPS-induced mitogen-activated protein kinase (MAPK) signaling, including ERK, p38, and JNK, in stromal cells. These results suggest that MDP might play an important role in pathological bone resorption in bacterial infection diseases.